2014
DOI: 10.1113/jphysiol.2014.284471
|View full text |Cite
|
Sign up to set email alerts
|

Large conductance Ca2+-activated K+channels (BK) promote secretagogue-induced transition from spiking to bursting in murine anterior pituitary corticotrophs

Abstract: Key points r Corticotroph cells of the anterior pituitary are electrically excitable and are an integral component of the hypothalamic-pituitary-adrenal axis which governs the neuroendocrine response to stress. r Corticotrophs display predominantly single spike activity under basal conditions that transition to complex bursting behaviours upon stimulation by the hypothalamic secretagogues corticotrophin-releasing hormone (CRH) and arginine vasopressin (AVP); however, the underlying mechanisms controlling burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…In the case of corticotrophs, acute exposure to the hypothalamic secretagogue CRH engages BK channels to promote the transition from single cell spiking that is blocked by early glucocorticoid feedback (Duncan et al . 2015, 2016), whereas in CS, as shown here, the increased spontaneous bursting activity is dependent upon BK channels being functional under non‐stimulated conditions. One of the important features of the regulation of excitability in CS is that overall the mean changes in several parameters of excitability are not significantly different but the variability across the population is much higher in corticotrophs from CS animals.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In the case of corticotrophs, acute exposure to the hypothalamic secretagogue CRH engages BK channels to promote the transition from single cell spiking that is blocked by early glucocorticoid feedback (Duncan et al . 2015, 2016), whereas in CS, as shown here, the increased spontaneous bursting activity is dependent upon BK channels being functional under non‐stimulated conditions. One of the important features of the regulation of excitability in CS is that overall the mean changes in several parameters of excitability are not significantly different but the variability across the population is much higher in corticotrophs from CS animals.…”
Section: Discussionsupporting
confidence: 54%
“…We have previously shown that increasing fast‐activating BK conductance facilitates bursting in corticotrophs (Duncan et al . 2015, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conductance-based models have been used to generate the spiking activity of electrically excitable cells including heart cells, pancreatic-beta cells and neurons and it has proved itself as a very successful tool to mimic the spiking activity and analyze the systems deeply [13][14][15].…”
Section: Introductionmentioning
confidence: 99%